Grade compulations on Paret’s set with two indexes - Lahuta, V. V. (Science and Transport Progress, 2011)
The problem of train traction calculations is considered as the one of resource allocation in a vector formulation. The solution is based on dynamic programming using a set of points of the optimal Pareto objective function values (energy, time).